Integrating Citizens’ Avatars in Urban Digital Twins. - García-Luque, Rafael; Toro-Gálvez, Lorenzo; Moreno, Nathalie; Troya-Castilla, Javier; Canal-Velasco, José Carlos; Pimentel-Sánchez, Ernesto (River Publishers, 2023)
Urban Digital Twins (UDT) represent a powerful tool to effectively make cities smart. Generally, UDTs are linked with other Digital Twins to build ecosystems where the citizen is at the heart of the ecosystem. This is why citizens should be considered first-class entities in the UDTs. At the same time, citizens’ privacy cannot be compromised. In this paper, we propose to integrate citizens’ digital twin in UDTs through their digital avatars (DAs). DAs allow exploiting citizens’ information, behavioral habits and personal preferences, while allowing them to have full control of their own data. We present our architecture that makes use of the Cloud-to-Thing Continuum to optimize available processing resources. We focus on a case study of the public transport service of the city of Malaga (Spain) and describe how we are approaching its implementation. Finally, we validate such UDT implementation through tests that evaluate its accuracy and the factors affecting its performance.
https://journals.riverpublishers.com/index.php/JWE/openaccess
Keywords: Internet de los objetos; Urban digital twin; Digital avatar; Cloud-to-thing continuum